(untitled) (Al-Academy, 2019)
The digital revolution had greatly affected the methods through which we communicate, starting from the basic concepts of the internet technology and the web content in addition to the important issues that concern the culture of the digital media, the internet governance and the variation in the digital age in general and the graphic and internal design in particular. This research addresses an important topic that goes along with the scientific development in the field of the digital design, especially in the internal and graphic designs. This study consists of two sections: the first includes the problem of the study and the need for it. Starting from the problem of the research, there is no clear perception of the formal characteristics for the digital graphic designs in the internal spaces and determining the roles in the design production between the internal designer and the graphic designer. Two objectives have been set for the research: The first is revealing the visual communication relations of the digital image and the internal graphic design and describing the results of the interaction between the modern digital techniques and the design. The second is presenting a scientific perception for the role exchange between the internal designer and the graphic designer. The current research is objectively limited to the residential internal spaces that use digital images that have been accomplished until the time of conducting this research. The research identified the terms used in the title of the research. It addresses a theoretical framework through three aspects: the first is the digital communication in the internal space, and the second is the virtual reality and the third is the graphic image and the internal virtual space. The research came up with conclusions the most important of which: 1- The digital image in the interior space simulates facts but according to the interpretation of the designer, and the desires of the space user. 2- The digital image in the internal space is produced by the work and common understanding between the graphic designer and the internal designer in order to reach the goal of the internal designer and to satisfy the desires of the internal space user. 3- The physical components of the internal space and visual digital image exchange roles in the perception of interior space and the integration of space so that the digital image would become part of the overall design of the interior space